Ease of Using a Dedicated Percutaneous Closure Device after Inadvertent Cannulation of the Subclavian Artery: Case Report - Arnaud Devriendt; Emmanuel Tran-Ngoc; Philippe Gottignies; José Castro-Rodriguez; Oliver Lomas; Sophie Jamart; Sébastien Knecht (Case Reports in Medicine)
Inadvertent puncture of the subclavian artery is a relatively frequent and potentially disastrous complication of attempted central venous access. Due to its noncompressible location, accidental subclavian arterial cannulation may result in hemorrhage as the sheath is removed. We report a new case of successful percutaneous closure of the subclavian artery which had been inadvertently cannulated, using a closure device based on a collagen plug (Angio-Seal, St. Jude Medical). This was performed in a patient who had received maximal antiplatelet and anticoagulation therapies because of prior coronary stenting in the context of cardiogenic shock. There was no prior angiographic assessment, as arterial puncture was presumed to have been distal to the right common artery and vertebral arteries. No complications were observed in this high-risk patient, suggesting that this technique could be used once the procedure has been evaluated prospectively.